(untitled) (Justicia &Derecho, 2022)
The 2030 agenda presents itself as an instrument designed to eradicate poverty in all its forms and dimensions, through the commitment of the 193 UN member states, which have committed themselves to the objectives of sustainable development. In this context, potable water and sanitation meet objective 6, which seeks to ensure the availability and sustainable management of water and sanitation for all. The problem with this investigation is centered on verifying whether there is a need for a paradigm shift in the current scenario of access to potable water in Brazil, to achieve universalization as a goal of the 2030 Agenda. current paradigm of the right to access to potable water; in the second, the analysis of this right as a human social fundamental and in the third, the realities and utopias for its universalization as a goal of the 2030 Agenda. As Base Theory and Approach the systemic-complete perspective is chosen, using authors with a multidisciplinary perspective on the connection of knowledge. The procedure used consists of a bibliographic analysis (in physical and digital media), and the technique employed involving the construction of reports and expanded summaries. It was verified that there is a need to change the paradigm of access to drinking water in Brazil, to recognize it as a fundamental social human outcome in the constitutional text, as a way of expanding the mechanisms of effective administrative protection in favor of the universalization of unhealthy public services. of potable water in line with the objectives of the 2030 Agenda.